Management of children with severe acute malnutrition: experience of nutrition rehabilitation centre at Baroda, Gujarat - Shah, Rinki H.; Javdekar, Bakul B. (International Journal of Contemporary Pediatrics, 2017)
Children with severe acute malnutrition, defined as weight for height <70% of reference median or bilateral pedal edema or midarm circumference <11 cm having complications were managed following the WHO guidelines, in the nutrition rehabilitation centre of medical college, Baroda. Total 60 children aged less than five years were admitted during October 2011 to September 2012. Of them majority were aged less than two years, & the predominant age presented was 6-12 months. Severe malnutrition is more among females. 86.65% & 5% study population formed by marasmus & kwashiorkor respectively. Most patients stayed for inpatients treatment between 16-20 days, mean duration of stay was 15.6 days. Reasons for bringing children to the hospital were associated major illnesses & complaint such as fever in 65% of patients, 40% had diarrhea. 96.6% had pallor, and associated co morbidities observed were bronchopneumonia followed by acute gastroenteritis. Observed complications of SAM in our study were hypoglycemia (5%), hypothermia (1.66%) some and severe dehydration were (18.33%) and (13.33%) respectively, hyponatremia (13.33%), hypokalemia (8.33%), hypernatremia (5%), hyperkalemia (1.66%), septic shock (11.6%), severe anemia (58.33%), congestive cardiac failure (28.5%). Majority of patients had weight for height between 61-70% on admission and between 71-80% on discharge. Average weight for height on admission was 68.5% and average weight for height on discharge was 77.2%. 29 % patients reached more than 90% weight for height. Mean weight gain was 9.3 gm/kg/day.78.33% patients who were admitted were discharged, 8.33% absconded, 5% expired. Case fatality rate in our study was 5%.